2019
DOI: 10.1021/acscatal.9b02987
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Trapping Strategy To Stabilize Subnanometric Pt Clusters for Highly Active Electrocatalysis

Abstract: Structure engineering is an effective way to substantially adjust the chemical and physical properties of materials. However, the effects of structure engineering of carbon hosts on the catalytic properties of Pt-based catalysts at the molecular scale are poorly understood. Herein, we report a molecular-level strategy to anchor and stabilize subnanometric Pt clusters on a covalently coupled host of graphitic carbon nitride (g-C3N4) and carbon nanotubes (CNT) for the development of electrocatalysts with high ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Reproduced with permission. [ 202 ] Copyright 2019, American Chemical Society. g) X‐ray photoelectron spectroscopy (XPS) Au 4f.…”
Section: D‐band Theory In the Electrocatalysis Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 202 ] Copyright 2019, American Chemical Society. g) X‐ray photoelectron spectroscopy (XPS) Au 4f.…”
Section: D‐band Theory In the Electrocatalysis Processesmentioning
confidence: 99%
“…Pt (Upshift of ε d ) : By anchoring Pt clusters on a covalently coupled support of g‐C 3 N 4 and carbon nanotubes, Chen et al have successfully realized the upshift of the d‐band center of Pt and thus strengthen the binding ability of the key intermediates to the electrocatalysts (Figure 19e). [ 202 ] The electrochemical performance of the electrocatalysts toward methanol oxidation has been comprehensively investigated. As expected, the Pt‐g‐C 3 N 4 ‐CNT shows the highest methanol oxidation current density of 19.45 mA cm –2 , which is much higher than those counterparts and the recently reported state‐of‐art electrocatalysts (Figure 19f).…”
Section: D‐band Theory In the Electrocatalysis Processesmentioning
confidence: 99%
“…Among reported noble-based catalysts, those based on the Pt metal are regarded as the star electrocatalysts for the AORs in terms of their oxidation overpotentials and Tafel slopes. [12,13] Notably, their alloys with other metals (e.g., Ru, Ni, Co, Pd, Rh, and Au) exhibit strong adsorption capability toward OH species or a so-called bifunctional mechanism, leading to improved AOR performance. [14][15][16][17] On the other hand, the serious poisoning effect of the carbonaceous intermediates (especially CO) hinders dramatically the activity of the used catalysts (especially the Pt catalysts) and eventually leads to much reduced conversion efficiencies of the AORs.…”
mentioning
confidence: 99%
“…The energy barrier in the multi-step reaction path is reduced in energy. 28 They all used melamine or urea and other precursors for the in situ doping of g-C 3 N 4 into the catalyst support and found that the stability and catalytic activity of the catalyst were greatly improved. Some researchers [29][30][31] prepared composite carriers by mechanical mixing.…”
Section: Introductionmentioning
confidence: 99%